Effects of hydrolyzed vegetable protein or hydrolyzed vegetable and meat protein blend on nursery pig performance from 15 to 40 lb - Goncalves, Marcio Antonio Dornelles; DeRouchey, Joel M.; Dritz, Steven S.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 280 pigs (PIC 327 × 1050, initially 16.7 lb BW) were used in a 28-d trial to evaluate the effects of hydrolyzed vegetable protein or a blend of hydrolyzed vegetable and meat protein for nursery pigs. Three days after weaning, pigs were allotted to 1 of 4 dietary treatments in a completely randomized design, balancing for initial BW and gender. There were 10 pens per treatment with 7 pigs per pen. The 4 treatment diets were: (1) no added specialty protein source (negative control); (2) 6% select menhaden fish meal; (3) 5% hydrolyzed vegetable protein (Hydr SF 52, International Ingredient Corporation, St. Louis, MO), or (4) 6.5% hydrolyzed vegetable and meat protein blend (HDSF Protein; International Ingredient Corporation). Diets were fed in 2 phases, with Phase 1 from d 0 to 17 (treatment diets) and Phase 2 from d 17 to 28 (common diet). From d 0 to 17, pigs fed the negative control diet had improved (P ≤ 0.05) F/G compared with pigs fed diets with Hydr SF 52 or HDSF Protein. No differences in ADG and ADFI were detected among treatments. From d 17 to 28 (common period), no difference was observed in growth performance between pigs previously fed any of the treatment diets. Overall (d 0 to 28), no differences were observed in ADG, ADFI, or F/G among pigs fed any of the treatment diets. Because performance did not differ from pigs fed the negative control diet, definitive conclusions regarding these specialty protein sources cannot be made.
Keywords: Hydrolyzed vegetable protein; Meat protein; Protein sources; Nursery pig